Comparison of the Intrusion Forces Generated by Intrusion Utility Arches According to Alloy Type, Wire Section and Activation Amount - An Invitro Study - كلش سعيد; جمال دباس (Latakia University Journal -Medical Sciences Series, 2023)
The aim of study: Evaluation of the intrusion forces resulting from Ricketts’ IUA Intrusion Utility Arches at different activation degrees using different alloys and wire sections - to know the importance of the type of alloy and wire section used to manufacture Intrusion Utility Arches. Materials and Methods: We used straight wires (recommended by the manufacturers of this arch) of stainless steel and Elgiloy alloys with two different section of 0.016 x 0.016 inch and 0.016 x 0.022 inch to make the Intrusion Utility Arches. Each sample consisted of 10 arches. An acrylic upper jaw model was used to perform the experiment. The arches were activated by 5-10-15-20 mm. Measured from the level of the anterior segment of the intrusion utility arch to the imaginary line representing the braces incision in the midline region, the amount of force produced was recorded at activation levels of 5-10-15-20 mm. Results The forces recorded at activation levels of 5-10-15-20 mm were all significant among the studied arches, and the current study confirmed that there was no difference between the stainless steel and blue elgiloy alloys, and the importance of choosing the intrusion utility arches section, as two different values of force were recorded when using either of the two sections at all levels of activation.